Qualitative Analysis of the Level of Satisfaction with Virtual Education in University Students in Times of Pandemic - Israel Barrutia Barreto (2021)
Introduction. Given the current global health context, people have changed their lifestyles according to the new health guidelines. In this sense, the education sector is one of the sectors that has made the most changes, since there has been an abrupt transition from face-to-face education to virtual education. However, this change has impacted college students in different ways. Goals. To describe the level of satisfaction with the new virtual education system by university students in Lima, during the Covid-19 pandemic. Methodology. The information was collected based on online surveys distributed via email and social networks, which were answered by a total of 10 students. The survey consisted of 8 questions focused on the degree of student satisfaction with the facilities in the use of computer tools provided by the university and the teaching style of teachers to transmit knowledge. Results and discussions. The students showed a moderate level of satisfaction with the classes received in the online mode. This is due to the lack of literacy in computer resources, especially in teachers. Likewise, many of them indicated that they are still not used to this new online modality, since they feel a greater workload. That is why, it is of utmost importance to continue improving the computer resources offered by the institution and for teachers to have training to offer a more didactic teaching and thus, to attract the attention of students. Conclusions. The results indicate that, for university students, adaptation to virtual education occurred progressively, from beginnings categorized as "difficult" towards "adaptation" to the new scheme, which they still perceive as deficient in relation to the face-to-face modality.